Strategi Penanggulangan Stunting di Nagari Labuah Panjang Kecamatan X Koto Diatas Kabupaten Solok Berbasis Posyandu: Studi Kasus Posyandu Mawar Melati - Muhammad Ichsan Kabullah; Desna Aromatica; Kusdarini Kusdarini; Hendri Koeswara; Malse Yulivestra (Warta Pengabdian Andalas, 2021)
Solok Regency is one of the regencies that occupy the highest prevalence of stunting in West Sumatra Province, with a total of 41.47% with details child's height of 15.77% concise and 25.70% short. The various negative impacts of stunting will be challenging to handle amid the current Covid-19 pandemic due to the increasing economic burden on families and poverty rates. It directly affects the increasing number of malnutrition children receive. A malnourished child gradually fails to achieve a standard and healthy height according to age. Stunting has an impact on reducing the IQ of children in Indonesia by 10 to 15 points. There needs to be a substantial effort to provide strategy in the context of stunting prevention so that the program of integrated community service post is directed measurably. These strategies are expected to generate a definite commitment from every policymaker to push down the stunting problem. The steps in this community engagement were problem identification, introducing innovation and best practices, and making an action plan. The recommended substantial efforts were massive media campaigns, increasing responsible personnel competence, and changing the Local Government Budget Planning pattern.